Serum progesterone distribution in normal pregnancies compared to pregnancies complicated by threatened miscarriage from 5 to 13 weeks gestation: a prospective cohort study - Chee Wai Ku; John C. Allen Jr; Sze Min Lek; Ming Li Chia; Nguan Soon Tan; Thiam Chye Tan (BMC, 2018)
Abstract Background Progesterone is a critical hormone in early pregnancy. A low level of serum progesterone is associated with threatened miscarriage. We aim to establish the distribution of maternal serum progesterone in normal pregnancies compared to pregnancies complicated by threatened miscarriage from 5 to 13 weeks gestation. Methods This is a single centre, prospective cohort study of 929 patients. Women from the Normal Pregnancy [NP] cohort were recruited from antenatal clinics, and those in the Threatened Miscarriage [TM] cohort were recruited from emergency walk-in clinics. Women with multiple gestations, missed, incomplete or inevitable miscarriage were excluded from the study. Quantile regression was used to characterize serum progesterone levels in the NP and TM cohorts by estimating the 10th, 50th and 90th percentiles from 5 to 13 weeks gestation. Pregnancy outcome was determined at 16 weeks of gestation. Subgroup analysis within the TM group compared progesterone levels of women who subsequently miscarried with those who had ongoing pregnancies at 16 weeks of gestation. Results Median serum progesterone concentration demonstrated a linearly increasing trend from 57.5 nmol/L to 80.8 nmol/L from 5 to 13 weeks gestation in the NP cohort. In the TM cohort, median serum progesterone concentration increased from 41.7 nmol/L to 78.1 nmol/L. However, median progesterone levels were uniformly lower in the TM cohort by approximately 10 nmol/L at every gestation week. In the subgroup analysis, median serum progesterone concentration in women with ongoing pregnancy at 16 weeks gestation demonstrated a linearly increasing trend from 5 to 13 weeks gestation. There was a marginal and non-significant increase in serum progesterone from 19.0 to 30.3 nmol/L from 5 to 13 weeks gestation in women who eventually had a spontaneous miscarriage. Conclusions Serum progesterone concentration increased linearly with gestational age from 5 to 13 weeks in women with normal pregnancies. Women with spontaneous miscarriage showed a marginal and non-significant increase in serum progesterone. This study highlights the pivotal role of progesterone in supporting an early pregnancy, with lower serum progesterone associated with threatened miscarriage and a subsequent complete miscarriage at 16 weeks gestation.